The effect of CORONA-COVID-19 on hospitality sector. Issue 1 (2nd January 2021) - Kumar, Sushil
Abstract: As most of the people knows that the Hospitality monster named after COVID-19, in the year 2020. The world has never thought about this evil which affects not only the life of a common man, but it destroying the job opportunities not even for India but for the whole world. The reason is the cold war between all over the world just to show the power & strength of the environment. Here is the result of a natural disaster, in the form of CORONA, COVID-19.As it is said by our ancestors & books, literature, research, etc. that nature is supreme power nobody has the weapon to defeat him. The paper will emphasize the current scenario for the hospitality sector & tourism sector as all of us are aware of the sector which is affected by the corona. The effect of the corona is not for just for months or years, but its effect is for years & years.